Revealing short-range non-Newtonian gravity through Casimir–Polder shielding. (28th March 2019) - Bennett, Robert; O'Dell, D H J
Abstract: We carry out a realistic, yet simple, calculation of the Casimir–Polder interaction in the presence of a metallic shield in order to aid the design of experiments to test non-Newtonian gravity. In particular, we consider a rubidium atom near a movable silicon slab with a gold film in between. We show that by moving the slab to various distances and making precise measurements of the force exerted on the atom, one could in principle discern the existence of short-range modifications to Newtonian gravity. This avoids the need for a patterned surface where calculations are much harder and for which the probe must be moved laterally at a fixed distance. We also briefly discuss the case where an atomic cloud undergoes Bloch oscillations within an optical lattice created by reflecting a laser off the shield. We find that our scheme has the potential to improve current constraints if relatively modest improvements in atom localisation in optical lattices are made.